Expresión de emociones y curso de la esquizofrenia - Gutiérrez, E.; Escudero, V.; Valero, J. A.; Vázquez, M. C.; Castro, J. A.; Álvarez, L. C.; Gómez, S. (Análisis y Modificación de Conducta, 1988)
Sin resumen